Perinatal Navigator Approach to Smoking Cessation for Women With Prevalent Opioid Dependence. (August 2019) - Fallin-Bennett, Amanda; Rademacher, Kathy; Dye, Holly; Elswick, Alex; Ashford, Kristin; Goodin, Amie
Women who smoke during pregnancy face psychosocial barriers to cessation, and women with opioid use disorder (OUD) face amplified barriers. We pilot tested a Perinatal Wellness Navigator (PWN) program for a group of high-risk perinatal women ( N = 50; n = 42 with OUD) that consisted of (a) one-on-one tobacco treatment, (b) comprehensive assessment of cessation barriers, and (c) linkage to clinical/social services. Outcome measures were assessed at baseline and postintervention. Participants smoked 10 fewer cigarettes per day ( p = .05) at postintervention and were less dependent on nicotine ( p < .01). Mean postnatal depression scores ( p = .03) and perceived stress ( p = .03) decreased postintervention. Participants received at least one referral at baseline ( n = 106 total), and 10 participants received an additional 18 referrals at postintervention to address cessation barriers. The PWN program was minimally effective in promoting total tobacco abstinence in a high-risk group of perinatal women, but participants experienced reductions in cigarettes smoked per day, nicotine dependence, stress, and depression.